2005
DOI: 10.1145/1066149.1066153
|View full text |Cite
|
Sign up to set email alerts
|

The effect of decision style on the use of a project management tool

Abstract: Managing a software development project presents many difficulties. Most software development projects are considered less than successful, and many are simply cancelled. Ineffective project management has been cited as a major factor contributing to these failures. Project management tools can greatly assist managers in tracking and controlling their projects. However, their structured and analytical nature does not necessarily match the decision-making styles of project managers.This paper presents the resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 31 publications
2
10
0
Order By: Relevance
“…Fox (1997) examined the effect of decision style on the use of project management software. He found that a project manager's decision style has a significant correlation with project management software usage.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Fox (1997) examined the effect of decision style on the use of project management software. He found that a project manager's decision style has a significant correlation with project management software usage.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The model has the following five variables that have been found to affect user satisfaction with IT: content, accuracy, format, ease of use, and timeliness. This model has been widely applied and found to be an accurate measure of user satisfaction (Fox, 1997).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Although their work points in the same direction as ours, they merely provide a general architecture that covers the functions that need to be addressed in this important application. Fox and Spence (2005) present an interesting study on the suitability of current project management tools to different cognitive strengths of individual PMs. Lee and Pena-Mora (2005) propose and implement the use of system dynamics in a simulation of a construction project.…”
Section: Cscw In Pm Supportmentioning
confidence: 99%
“…Their granularity is varied, from fine-grained low data files or messages to tacit knowledge that cannot easily be formed into a document that has explicit descriptions of them. There are already many researches about better information sharing in organizations [9], [10], [11], [12]. However, their early discussions were on a static organization whose members may have different c 2012 Information Processing Society of Japan interests.…”
Section: Introductionmentioning
confidence: 99%